Q. 134.7( 3 Votes )

# If the sum of the roots of a quadratic equation is 6 and their product is 6, the equation isA. x2 - 6x + 6 = 0B. x2 + 6x - 6 = 0C. x2 - 6x - 6 = 0D. x2 + 6x + 6 = 0

Answer :

Sum = 6 and Product = 6

Quadratic equation = x2 –Sum x + Product = 0

= x2 - 6x + 6 = 0

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Get To Know About Quadratic Formula42 mins
Quiz | Knowing the Nature of Roots44 mins
Take a Dip Into Quadratic graphs32 mins
Foundation | Practice Important Questions for Foundation54 mins
Nature of Roots of Quadratic EquationsFREE Class
Getting Familiar with Nature of Roots of Quadratic Equations51 mins
Quadratic Equation: Previous Year NTSE Questions32 mins
Champ Quiz | Quadratic Equation33 mins
Balance the Chemical Equations49 mins
Champ Quiz | Quadratic Equation48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses